2008
DOI: 10.1111/j.1600-6143.2008.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pegylated Interferon and Ribavirin Treatment on Graft Survival in Liver Transplant Patients with Recurrent Hepatitis C Infection

Abstract: Recurrent hepatitis C virus (HCV) infection is a major cause of morbidity and mortality after liver transplantation for HCV-related end stage liver disease.Although previous studies have shown a short-term effect of interferon-based treatment on fibrosis progression, it is unclear whether this translates to improved graft survival. We evaluated whether treatment of recurrent HCV leads to an improved graft survival. Cohort study included consecutive HCV patients who underwent liver transplantation between 1 Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 20 publications
4
63
1
1
Order By: Relevance
“…On the other hand, they stress that patients with high liver stiffness 12 months after LT are at high risk of losing their graft, thus HCV eradication should be prompted in this population. Our results support previous studies that demonstrated that SVR to antiviral therapy after transplantation results in improved clinical outcomes (8)(9)(10)(11), and reveal that the improvement in survival is mainly driven by those patients with a more severe recurrence (those with high LSM 1 year after LT). This population should be the main target to undergo treatment with new direct acting antivirals.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, they stress that patients with high liver stiffness 12 months after LT are at high risk of losing their graft, thus HCV eradication should be prompted in this population. Our results support previous studies that demonstrated that SVR to antiviral therapy after transplantation results in improved clinical outcomes (8)(9)(10)(11), and reveal that the improvement in survival is mainly driven by those patients with a more severe recurrence (those with high LSM 1 year after LT). This population should be the main target to undergo treatment with new direct acting antivirals.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, recurrent hepatitis C accounts for most graft losses after LT. Patients undergoing antiviral therapy with pegylated interferon and ribavirin after transplantation achieve sustained virological response (SVR) in only 30-35% of cases (6,7) but, importantly, SVR is associated with a significant improvement in clinical outcomes (8)(9)(10)(11). For these reasons, identification of hepatitis C virus (HCV)-infected LT recipients who are at risk of losing their graft (''rapid fibrosers'') is crucial in order to indicate antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although IFN-centered antiviral therapy is significantly associated with post-transplantation graft prognosis in patients infected with HCV, 22 the efficacy of the IFN therapy after orthotopic liver transplantation (OLT) is unsatisfactory 23 and the treatment is frequently accompanied by severe side effects. 24 Therefore, in addition to the development of an optimal therapeutic regimen for HCV infection after OLT, establishment of a reliable marker or set of markers to predict the sensitivity to IFN therapy is needed.…”
Section: Il-28b Variation and The Association With Response To Hcv Anmentioning
confidence: 99%
“…Several reports have shown that post-OLT patient and graft survival are significantly negatively affected by HCV recurrence after OLT [92,93]. This can be mitigated by achievement of an SVR with PEG-IFN plus RBV therapy [94]. However, many patients cannot tolerate curative doses or do not respond to therapy [93][94][95].…”
Section: Molecular Epidemiology Of Hcv-relatedmentioning
confidence: 99%
“…This can be mitigated by achievement of an SVR with PEG-IFN plus RBV therapy [94]. However, many patients cannot tolerate curative doses or do not respond to therapy [93][94][95]. Therefore, as it would be ideal to be able to predict which patients would benefit from PEG-IFN plus RBV therapy for recurrent HCV, it was recently reported that variants of the SNPs in or around the IL-28B gene from liver donors are also strongly associated to the degree of graft inflammation and the response to therapy of HCV-infected liver recipients [96][97][98].…”
Section: Molecular Epidemiology Of Hcv-relatedmentioning
confidence: 99%